3. INCREASE SURVIVAL OF LACTOBACILLUS ACIDOPHILUS IN ALGINAT - CHITOSAN MICROCAPSULES (Vietnam Journal of Community Medicine, 2023)
Objective: In addition to evaluating some of the encapsulated microencapsulation’s properties and its capacity to both protect and release microorganisms in the simulated gastrointestinal system, this study intends to investigate the parameters of the encapsulation process. Research subjects and methods: Lactobacillus acidophilus was encapsulated in alginate and chitosan using the coagulation methods to create microcapsules to avoid the harsh environment in the stomach. Results: The density of microscopic organisms encapsulated in the nuclear microencapsulation AC-1 is 9,35±0,30 log CFU/g and the density of microscopic organisms in the nuclear microencapsulation A is 9,24±0,50 log CFU/g. As a result, nuclear microcapsules and encapsulated microcapsules were prepared using alginate-chitosan FAO/WHO requirements for probiotic goods. After 2 hours in SGF, nuclear microcapsules A released 13,10% of the VSV compared to the original, while nuclear microcapsules AC-1 released 11,66%. This was done to assess the protective ability of SGF and release in SIF. Nuclear microcapsule A released the most microscopic organisms after two hours in SIF (81,66%), while nuclear microencapsulation AC-AC released the least (60,35%). After three hours in SIF, A-A microcapsules produced the least amount of VSV (75,41%), while AC-AC microcapsules released the most (85,95%). Conclusion: This outcome demonstrates that the alginate-chitosan coating protects bacteria and extends their release period in the gastrointestinal tract. L. acidophilus - containing alginatechitosan microcapsules preserved and improved the survival of microorganisms after freeze-drying, throughout storage, and in a model of the gastrointestinal tract of SGF and SIG. The encapsulated microcapsules’ structural stability is increased for a longer period of time when they are coated with alginate and chitosan in a setting that mimics intestinal fluid.
Keywords: Alginate – chitosan, encapsulation, L. acidophilus, probiotic, survival.